HUBUNGAN PEMENUHAN KEBUTUHAN SPIRITUAL DENGAN TINGKAT KECEMASAN PASIEN GAGAL GINJAL KRONIK STAGE V YANG MENJALANI TERAPI HEMODIALISA (STIKES Telogorejo Semarang, 2022)
Chronic Kidney Disease stage V is a final stage renal disease with progressive and irreversible features. The indications are the body's incapability to keep the metabolism and the failure to keep the liquid balance. Chronic Kidney Disease stage V patients with hemodialysis therapy may suffer from anxiety due to the death and the final result of the committed therapy. This research analyzed the spiritual need fulfillment of the patients and the anxiety levels of chronic kidney disease stage V patients with hemodialysis therapy. This cross-sectional research took 62 respondents as the samples with a purposive sampling technique. The Spearman test obtained a p-value of 0.000 lower than 0.05. The value indicated a significant correlation between spiritual necessity fulfillment and the anxiety levels of chronic kidney disease stage V patients with hemodialysis. The result showed that most respondents did not have spiritual necessity fulfillment, 33 respondents (52.2%). Then, respondents with moderate anxiety consisted of 32 respondents, 51.6%. The results could be further references for future researchers to develop related spiritual necessities for chronic kidney disease stage V patients.